Studies of light exotic nuclei in the vicinity of neutron and proton drip lines at FLNR JINR. (April 2016) - Grigorenko, L V; Golovkov, M S; Krupko, S A; Sidorchuk, S I; Ter-Akopian, G M; Fomichev, A S; Chudoba, V
Abstract: Defining the limits of the existence of the nuclear structure is one of fundamental problems of natural science, requiring the advancement of studies towards the sites of maximum neutron- and proton-excess nuclei, to the borders of nuclear stability, and further, to the regions of nuclear instability. In such regions, nuclear systems exist only as resonant states in continuous spectra with characteristic 'nuclear' lifetimes. This work is done most effectively with experimental setups providing radioactive ion beams (RIBs). This review discusses the approaches in this field of research developed during the last at the ACCULINNA fragment separator in the Flerov Laboratory of Nuclear Reactions (FLNR) of the Joint Institute for Nuclear Research (JINR). The methodology developed is based on the comprehensive study of correlations among the reaction fragments emitted in the decays of nuclear-unstable systems which are populated in direct reactions induced by RIBs with intermediate ( per nucleon) energies. This allows us to acquire detailed knowledge about exotic nuclear systems close to and beyond nuclear drip lines. We discuss exotic forms of nuclear dynamics appearing in the vicinity of nuclear drip lines and relevant results of their theoretical analysis. Also discussed are existing facilities and prospective projects aimed at nuclear structure studies with RIBs at JINR.